Impacts and Problems of Early Marriage During The Covid-19 Pandemic - Yuli Sri Handayani; Muhammad Faqih Urrahman; Muhammad Izzul Haq; Farezza Nur Pahlevi; Dzaki Almas Akbar; Yaafi’ Azhar (Magister Ilmu Hukum Fakultas Hukum Universitas Syiah Kuala, 2021)
The aim of this research is to explain the factor and the impact of young married people. In this COVID-19 pandemic, there are so many Indonesian teenagers doing married in the young age. Factors that influence the increase of this issue is becaused of exonomy, religion, and promiscuity. People who do this thing must ready to face all of problem and impact that will happen because everything getting worse in this pandemic Covid-19 actually in economic.